2019
DOI: 10.3171/2019.5.focus1947
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endoscopic sinus surgery for sinusitis-induced intracranial abscess in patients undergoing neurosurgery

Abstract: OBJECTIVEAlthough sinusitis-induced intracranial complications rarely occur in the current era of antibiotics, they can induce neurological symptoms or death. The authors of this study investigated the association between endoscopic sinus surgery (ESS) and outcomes in patients who had undergone neurosurgical procedures for sinusitis-induced intracranial abscess.METHODSThe authors obtained data on patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…The authors concluded that ESS does not add substantially to a reduction in mortality, readmission rates, reoperation rates, or length of hospital stay in patients with SIIA requiring neurosurgical intervention. 4 These conclusions are in contrast to some previously published reports 2,5 and are supported by others. 1,3 Koizumi et al 4 investigated the association between outcomes in patients undergoing neurosurgical interventions for SIIA and an ESS performed within the same hospitalization.…”
mentioning
confidence: 55%
See 4 more Smart Citations
“…The authors concluded that ESS does not add substantially to a reduction in mortality, readmission rates, reoperation rates, or length of hospital stay in patients with SIIA requiring neurosurgical intervention. 4 These conclusions are in contrast to some previously published reports 2,5 and are supported by others. 1,3 Koizumi et al 4 investigated the association between outcomes in patients undergoing neurosurgical interventions for SIIA and an ESS performed within the same hospitalization.…”
mentioning
confidence: 55%
“…4 These conclusions are in contrast to some previously published reports 2,5 and are supported by others. 1,3 Koizumi et al 4 investigated the association between outcomes in patients undergoing neurosurgical interventions for SIIA and an ESS performed within the same hospitalization. The study design was retrospective in nature, and data on the patients with SIIA were collected from a large administrative nationwide inpatient database over a period of 8 years.…”
mentioning
confidence: 55%
See 3 more Smart Citations